Design of Self-Propelled Container Barge for Logistics Transportation of Samarinda-Kotabangun - Pawara, Muhammad Uswah; Setiawan, Wira; Alamsyah, Alamsyah; Suardi, Suardi; Ramadhani, Rizky (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2021)
currently general cargo transportation using containers is preferred. There are many reasons for choosing a container compared to normal cargo transportation, some of the reasons are having a standardized protection system, so it is safer to protect cargo. On the Samarinda - Kota Bangun route, transportation for logistics distribution uses the truck transportation mode. In this mode of transportation, it is highly influenced by traffic conditions and the roads in which it passes. For this reason, the use of self-propelled container barges (SPCB) is considered very efficient because it can overcome problems in container transportation rather than using land transportation modes. To get the design of a self-propelled container barge ( SPCB) the main size of the ship is obtained from the ratio of the main size of the ship. Then make a Line Plan with Maxsurf software and make a general plan with Autocad software and the main measurements obtained are; Lpp = 83.7 m; Lwl = 87.04 m; B = 12 m; H = 6 m; T = 4.5 m; VS = 10 knot; D = 4383 ton. With the number of containers as much as 140 Teus, the largest trim occurs at 0% DWT, namely 0.611 m stern trim. All the stability criteria of IMO A 749 (18) meet the 4 variations of the weight of the ship. In the DWT condition 100% the GZ max value is 0.512 m at an angle of 27.3○, and in the DWT condition 50% the GZ max value is 1.717 m at an angle of 38.2○ and at 25% DWT condition the GZ max value is 2.454 m occurs at an angle of 40.9○, and at 0% DWT condition, the maximum GZ value is 2.674 m occurs at an angle of 25.5○.